Argumentative Voice in English Eighteenth-Century Translations of Jean-Jacques Rousseau’s Du contrat social (1762) - Jooken, Lieve (TTR)

(untitled) (Association canadienne de traductologie, 2021)
This study compares two contemporary English translations of one of Jean-Jacques Rousseau’s major works on the nature of society and the institution of political sovereignty, Ducontrat social; ou principes du droit politique (1762). The case study intends to elucidate the extent and nature of translators’ interpretative discursive presence in their rendering of philosophical discourse. The analysis considers a selection of excerpts in source and target texts and traces instances of the implicit argumentative mediation of the translator, which mainly surfaces in the addition of rhetorical emphasis (amplificatio) and the explicit expression of implied meaning, but also in the alteration of denotation and down toning or omission of arguments (brevitas). The discussion reveals that both the 1764 and 1791 translations of the Social Contract primarily render the author’s arguments in a more emphatic and explicit tenor, which indicates the translators’ “associative attitude” (Hermans, 2010) to the discourse represented. The 1791, “revolutionary” rendering of Du contrat social moreover shifts the meaning of the proposition in places by introducing a clearer connotation of despotism in references to royal power.